A Survey of Freshwater Fish Fauna in the Upper Rivers of Crocker Range National Park Sabah, Malaysia - Khairul Adha, A. Rahim; Shabdin, Mohd Long; Fatimah, Abang (ARBEC Publishing, 2002)
The fish fauna distribution in six rivers in the Crocker Range National Park was examined. All the six rivers surveyed were generally shallow, fast flowing with clear water and rocky and sandy substrate. At the time of survey, all rivers gave excellent water quality data. A total of 17 fish species belonging to four families were sampled. The gastromyzontids represented the major species in all the rivers surveyed, comprising 59.5% of the total number of fish caught. Commercially valuable fish such as the Tor species was also found in the rivers studied.